Multiple Solutions to the Same Problem: Utilization of Plausibility and Syntax in Sentence Comprehension by Older Adults with Impaired Hearing - Amichetti, Nicole M.; White, Alison G.; Wingfield, Arthur (Frontiers in Psychology, 2016)
A fundamental question in psycholinguistic theory is whether equivalent success in sentence comprehension may come about by different underlying operations. Of special interest is whether adult aging, especially when accompanied by reduced hearing acuity, may shift the balance of reliance on formal syntax versus plausibility in determining sentence meaning. In two experiments participants were asked to identify the thematic roles in grammatical sentences that contained either plausible or implausible semantic relations. Comprehension of sentence meanings was indexed by the ability to correctly name the agent or the recipient of an action represented in the sentence. In Experiment 1 young and older adults’ comprehension was tested for sentences with the meaning expressed with either an active-declarative or a passive syntactic form. In Experiment 2 comprehension performance was examined for young adults with age-normal hearing, older adults with good hearing acuity, and age-matched older adults with mild-to-moderate hearing loss for plausible or implausible sentences with meaning expressed with either a subject-relative or an object-relative syntactic structure. Experiment 1 showed that the likelihood of interpreting a sentence according to its literal meaning was reduced when that meaning expressed an implausible relationship. Experiment 2 showed that this likelihood was further decreased for object-relative as compared to subject-relative sentences, and especially so for older adults whose hearing impairment added to the perceptual challenge. Experiment 2 also showed that working memory capacity as measured with a letter-number sequencing task contributed to the likelihood that listeners would base their comprehension responses on the literal syntax even when this processing scheme yielded an implausible meaning. Taken together, the results of both experiments support the postulate that listeners may use more than a single uniform processing strategy for successful sentence comprehension, with the existence of these alternative solutions only revealed when literal syntax and plausibility do not coincide.